2005
DOI: 10.1158/1078-0432.ccr-05-1074
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Melanoma at an Early Stage Based on the Increased Serum Secreted Protein Acidic and Rich in Cysteine and Glypican-3 Levels

Abstract: Purpose: There are no available tumor markers detecting primary melanoma at an early stage.The identification of such serum markers would be of significant benefit for an early diagnosis of melanoma.We recently identified glypican-3 (GPC3) as a novel tumor marker but could diagnose only 40% of melanomas. Thereby, we focused out attention on secreted protein acidic and rich in cysteine (SPARC) overexpressed in melanoma as another candidate for tumor marker. Experimental Design: Secreted SPARC protein was quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 34 publications
4
48
0
Order By: Relevance
“…Paracrine functions attributed so far to SPARC in melanoma were related to inhibition of polymorphonuclear leukocyte recruitment 43 , and inhibition of proliferation and migration capacities of endothelial cells in vitro 45 . Supported by previous evidence that elevated SPARC is associated with the occurrence of distant metastases and poor survival in melanoma patients 30,31 , our findings functionally demonstrate that SPARC mediates critical tumour cell-endothelium communications through a novel paracrine function on lung capillaries culminating in breaching vascular integrity during metastatic dissemination. Clinically, our findings are underlined by the high expression of SPARC that we observed in pulmonary metastases of melanoma biopsies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Paracrine functions attributed so far to SPARC in melanoma were related to inhibition of polymorphonuclear leukocyte recruitment 43 , and inhibition of proliferation and migration capacities of endothelial cells in vitro 45 . Supported by previous evidence that elevated SPARC is associated with the occurrence of distant metastases and poor survival in melanoma patients 30,31 , our findings functionally demonstrate that SPARC mediates critical tumour cell-endothelium communications through a novel paracrine function on lung capillaries culminating in breaching vascular integrity during metastatic dissemination. Clinically, our findings are underlined by the high expression of SPARC that we observed in pulmonary metastases of melanoma biopsies.…”
Section: Discussionsupporting
confidence: 84%
“…Despite earlier studies that have correlated levels of SPARC to the early stages of malignant melanomas and found expression of SPARC associated with invasion and poor clinical income [30][31][32] , no evidence has been provided for an association of SPARC with distant melanoma metastases. To determine the clinical relevance of our findings, we investigated SPARC expression in human melanoma lung metastases and amounts of circulating SPARC in blood from patients with stage 4 metastatic disease.…”
Section: Tumour-derived Sparc Induces Vascular Permeability In Vitromentioning
confidence: 93%
“…Glypican-3 (GPC3) is a membrane-bound heparin sulfate proteoglycan which is overexpressed in several tumors. It has been suggested that GPC3 may be a useful early stage biomarker for patients with the early stages of the disease (0 -II) (Nakatsura et al, 2004;Ikuta et al, 2005). Moreover, cyclooxygenase-2 (COX-2) (Chwirot and KuĆșbicki, 2007), serum amyloid A (SAA) (Mian et al, 2005;Findeisen et al, 2009) and DNA methylation profiling (Conway et al, 2011) can be used to distinguish between early melanomas and benign nevi.…”
Section: Biomarkers For Early Melanoma Diagnosismentioning
confidence: 99%
“…During hepatic carcinogenesis, GPC3 have been reported to reappear in HCC and to be released into serum (12,13,15,26). Its expression is also detected in melanoma (27)(28)(29). The functions of GPC3 in cancer cells are still unclear.…”
Section: Glypican-3 Is a Useful Diagnostic Marker For A Component Of mentioning
confidence: 99%